The linear correlation research in paired small volume samples - Popukaylo, V. S. (Technology and design in electronic equipment, 2016)
This article describes the methods of finding the values of the linear correlation in paired small volume samples. The importance of the study lies in the fact that in problems of technical control, it is not always possible to obtain a data set sufficiently large for traditional analysis methods. In this research the author investigates and visually illustrates the possibility of Pearson correlation coefficient usage (and the impact on the value of the virtual procedures increasing the volume sample), as well as the possibility of the Fechner’s modified index usage after applying the method of pointed distributions and tabulation of the virtual two-dimensional distribution. The study allows concluding that the considered methods do not provide the required accuracy on small volume samples, and the usage of “bootstrapping” and the method of point distributions during the correlation analysis are not recommended here.